Kandungan Gizi dan Daya Terima Formula Tortila Chips dengan Penambahan Tepung Jamur Sawit (Volvariella Volvacea) sebagai Alternatif Snack untuk Anak Usia Sekolah - Rendy Murdiyanto Langkamuda; Hardianti Hardianti; Nurdiana Nurdiana; Ni Ketut Kariani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Nutrition is crucial for children's growth and development. Protein Energy Deficiency (PEM) is a common nutritional problem among elementary school-aged children and can impact their health, growth, and cognitive development. The prevalence of PEM among toddlers in Indonesia reached 17.9% in 2013. Palm Mushrooms, which are rich in macronutrients, can be a solution to this problem. Therefore, efforts are needed to address PEM through the consumption of nutritious foods, such as tortilla chips supplemented with palm mushroom flour. The purpose of this study was to analyze the acceptability and nutritional content of tortilla chips supplemented with palm mushroom flour (Volvariella volvacea) as an alternative snack for school-aged children. This study used an experimental design with a Completely Randomized Design (CRD) method, involving three treatments and two replications. The results of the organoleptic test showed that formulation 2, namely tortilla chips supplemented with palm mushroom flour, received a significant value (p<0.05) for color, aroma, taste, and texture, indicating a significant effect of the addition of palm mushroom flour on tortilla chips. Laboratory and organoleptic tests showed significant values ​​(p<0.05) for moisture, ash, carbohydrate, and protein content, indicating a significant effect of the addition of palm mushroom flour. Future researchers are expected to test the shelf life of tortilla chips made from palm mushroom flour.